Conversion of left-over ice cream into bakery product for food sustainability - Jamaludin, N. S.; Samsu Baharuddin, Azhari; Ab Karim, Muhammad Shahrim; Wakisaka, Minato; Abd Rahman, Nur 'Aliaa (Rynnye Lyan Resources, 2021)
Food sustainability has become so important nowadays not only in order to ensure all raw materials are converted into food for consumption, but also to recycle leftover food for gastronomy. The innovative product created from leftover or unfinished food is a good alternative to throwing away food by-products. In this study, the unutilized ice cream post-selling or post-production process was reformulated with other ingredients to produce bakery products such as cake. Four different cake formulations were used which consisted of melted leftover ice cream, instant cake mix and eggs. The physical qualities of the samples were investigated, and sensory evaluation was also conducted. Cake made conventionally from instant cake mix without the addition of the leftover ice cream was used as a control sample in this study. Cake produced from melted ice cream using three eggs (sample A) had the highest moisture content among all samples which was 39.09%. The control sample had the highest specific volume (2.99 cm3/g) which indicated a high amount of air remained in the structure after baking. All samples showed a positive symmetry index which indicated good expansion except for cake produced from melted ice cream with no egg (sample D). Cake produced from melted ice cream with no egg (sample D) had the lowest firmness as compared to other cake samples. Cake produced using melted ice cream which contained two eggs (Sample B) had the highest value of springiness which was 0.94 mm. A plot of chewiness as a function of firmness with an R2 value of 0.9887 confirms the positive correlation between firmness and chewiness. From the sensory evaluation conducted, the cake produced from melted ice cream using three eggs (sample A) scored the highest mark for colour, aroma, sweetness, taste and overall acceptability among the formulated cakes. The results suggested that using melted ice cream as the base ingredient for cake making would tremendously help in solving food waste created by the by-product of the ice cream business and turn it into profit.